2020
DOI: 10.26599/jnr.2020.9040014
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation for pediatric patients with drug-resistant epilepsy caused by genetic mutations: Two cases

Abstract: Vagus nerve stimulation (VNS) is a neuromodulation therapy increasingly used for treating drug-resistant epilepsy. However, it remains to be determined which patients are best suited for the treatment, and it is difficult to predict the therapeutic effect before the implantation. Mutations in some genes could lead to epilepsy. Here we report two cases of pediatric patients with drug-resistant epilepsy treated by VNS therapy: Patient 1 with ARX mutation achieved good outcomes; Patient 2 with the CDKL5 mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally acknowledged that epilepsy surgery and neuromodulation surgery are effective therapies to treat refractory epilepsy [3,4]. Recent studies have shown that neurostimulation has also become one of the effective therapies for refractory epilepsy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…VNS is a minimally invasive and controllable treatment for patients with epilepsy, and there are approximately 45%–65% responders (⩾50% reduction in seizure frequency) after VNS therapy. 8 12 In addition, indications, 13 15 safety, and side effects 16 , 17 of VNS therapy have been internationally validated and acknowledged. Some patient-related and epilepsy-related predictors with an impact on the prognosis of VNS therapy have been proposed.…”
Section: Introductionmentioning
confidence: 99%